The Dynamics of Javanese Weton Calculation in Wedding Planning - Wahyudin, Muhamad; Syafe’i, Zakaria; Ma’rifah, Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the practice of Weton calculation in Javanese marriages, focusing on cultural, social, and legal aspects. This cultural heritage is significant for the Javanese community, reflecting local wisdom and social norms respected in marriage. However, in the modern era, this tradition faces challenges that alter societal values and mindsets. The alignment of Weton is considered crucial for marital success, while mismatches can negatively impact family life. This research employs a transdisciplinary approach, involving anthropology, astrology, and the sociology of religion, to understand the role of Weton in social structure and religious interactions. Although Weton holds deep meaning in Javanese culture, the practice conflicts with Islamic teachings, which view it as heresy and magical manipulation. This qualitative study, based on library research, highlights the importance of religious context in understanding the Weton practice